Radiosynthesis and in vivo evaluation of a fluorine-18 labeled pyrazine based radioligand for PET imaging of the adenosine A2B receptor. Issue 16 (1st September 2018) - Lindemann, Marcel; Hinz, Sonja; Deuther-Conrad, Winnie; Namasivayam, Vigneshwaran; Dukic-Stefanovic, Sladjana; Teodoro, Rodrigo; Toussaint, Magali; Kranz, Mathias; Juhl, Cathleen; Steinbach, Jörg; Brust, Peter; Müller, Christa E.; et al.
Graphical abstract: Abstract: On the basis of a pyrazine core structure, three new adenosine A2B receptor ligands (7a –c ) were synthesized containing a 2-fluoropyridine moiety suitable for 18 F-labeling. Compound 7a was docked into a homology model of the A2B receptor based on X-ray structures of the related A2A receptor, and its interactions with the adenosine binding site were rationalized. Binding affinity data were determined at the four human adenosine receptor subtypes. Despite a rather low selectivity regarding the A1 receptor, 7a was radiolabeled as the most suitable candidate ( K i (A2B ) = 4.24 nM) in order to perform in vivo studies in mice with the aim to estimate fundamental pharmacokinetic characteristics of the compound class. Organ distribution studies and a single PET study demonstrated brain uptake of [ 18 F]7a with a standardized uptake value (SUV) of ≈1 at 5 min post injection followed by a fast wash out. Metabolism studies of [ 18 F]7a in mice revealed the formation of a blood–brain barrier penetrable radiometabolite, which could be structurally identified. The results of this study provide an important basis for the design of new derivatives with improved binding properties and metabolic stability in vivo.